Claudin7b is required for the formation and function of inner ear in zebrafish. Issue 4 (27th September 2017) - Li, Xiaohui; Song, Guili; Zhao, Yasong; Zhao, Feng; Liu, Chunyan; Liu, Dong; Li, Qing; Cui, Zongbin
Abstract : Zebrafish has become an excellent model for studying the development and function of inner ear. We report here a zebrafish line in which claudin 7b ( cldn7b ) locus is interrupted by a Tol2 transposon at its first intron. The homozygous mutants have enlarged otocysts, smaller or no otoliths, slowly formed semicircular canals, and insensitiveness to sound stimulation. These abnormal phenotypes and hearing loss of inner ear could be mostly rescued by injection of cldn7b ‐mRNA into one‐cell stage homozygous mutant embryos. Mechanistically, cldn7b ‐deficiency interrupted the formation of apical junction complexes (AJCs) in otic epithelial cells of inner ear and the ion‐homeostasis of endolymph, which then led to the loss of proper contact between otoliths and normally developed hair cells in utricle and saccule or aberrant mechanosensory transduction. Thus, Cldn7b is essential for the formation and proper function of inner ear through its unique role in keeping an initial integrity of otic epithelia during zebrafish embryogenesis. Abstract : We report a zebrafish line in which Cldn7b gene is interrupted by a Tol2 transposon. Homozygous cldn7b ‐mutants have enlarged otocysts, smaller or no otoliths, slowly formed semicircular canals, and insensitiveness to sound stimulation. Mechanistically, Cldn7b ‐deficiency interrupted the formation of apical junction complexes in otic epithelial cells of inner ear and the ion‐homeostasis of endolymph, leading to the loss of proper contact between otoliths and normally developed hair cells in utricle and saccule and aberrant mechanosensory transduction.